Perpetradores de violações aos direitos humanos na ditadura militar brasileira: análise em ações penais do Ministério Público Federal - Silva, Alexsander de Carvalho (2019)
The present research aimed to analyze the performance of perpetrators of human rights violations in the Brazilian military dictatorship, which lasted from 1964 to 1985. The analysis was made in 31 criminal prosecutions of the Federal Public Prosecution Office, filed between 2012 and 2018, against 45 State agents for crimes committed in the dictatorship. The methodology used was the Grounded Theory, through which codes and categories are generated. The coding of the actions resulted in 454 generated codes that formed seven analytical categories: System, Opponent's View, Narrative Making, Banality of Evil, Discipline of the Bodies, Suffering, and Crimes against Humanity. The analysis of the categories showed that the military dictatorship installed a sophisticated system of repression of the opponents of the regime that was responsible for arrests, torture, deaths and forced disappearances. The perpetrators of the system committed violent and cruel acts for which they have not yet been punished. The Federal Prosecutor's Office has sought punishment by characterizing violations as a crime against humanity.